ANALISIS AKUNTABILITAS PROGRAM KELUARGA HARAPAN (Studi Deskriptif Akuntabilitas Administratif Pelaksanaan Program Keluarga Harapan Bidang Pendidikan di Kecamatan Semampir Surabaya) - Yuni Aliyatul Rohmah (Faculty of Social and Political Science, 2015)
“Program Keluarga Harapan” is one of the poverty reduction program that provides funds to help very poor families with specific criteria and requires that participants meet the obligations in the field of education and health. The implementation of the Program Keluarga Harapan in Semampir still found some problems such as participants who do not meet the criteria of PKH. The purpose of this research is to describe and analyze the administrative accountability of the Program Keluarga Harapan (PKH) in subdistrict Semampir Surabaya. This research is a descriptive qualitative research through observation, interview and documentation. Based on the research results can be known that the implementation of the Program Keluarga Harapan in district Semampir has fulfill administrative accountability, but on criteria and mechanisms indicators in the administrative accountability are still not fulfilling the administrative accountability, and there is the factor that supports the implementation of the Program Keluarga Harapan, namely clarity of procedures, and there are external parties which supervise the implementation of the Program Keluarga Harapan.